A Probabilistic Model of Social Choice - Intriligator, M. D. (Review of Economic Studies, 1973)
Journal Article A Probabilistic Model of Social Choice Get access Michael D. Intriligator Michael D. Intriligator University of California, Los Angeles Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 40, Issue 4, October 1973, Pages 553–560, https://doi.org/10.2307/2296588 Published: 01 October 1973